Personalized Models of Search Satisfaction - Awadallah, Ahmed; White, Ryen W. (ACM International Conference on Information and Knowledge Management (CIKM), 2013)
Search engines need to model user satisfaction to improve their services. Since it is not practical to request feedback on searchers’ perceptions and search outcomes directly from users, search engines must estimate satisfaction from behavioral signals such as query refinement, result clicks, and dwell times. This analysis of behavior in the aggregate leads to the development of global metrics such as satisfied result clickthrough (typically operationalized as resultpage clicks with dwell time exceeding a particular threshold) that are then applied to all searchers’ behavior to estimate satisfaction levels. However, satisfaction is a personal belief and how users behave when they are satisfied can also differ. In this paper we verify that searcher behavior when satisfied and dissatisfied is indeed different among individual searchers along a number of dimensions. As a result, we introduce and evaluate learned models of satisfaction for individual searchers and searcher cohorts. Through experimentation via logs from a large commercial Web search engine, we show that our proposed models can predict search satisfaction more accurately than a global baseline that applies the same satisfaction model across all users. Our findings have implications for the study and application of user satisfaction in search systems.